Multiple-Product Firms and Product Switching - Bernard, Andrew B; Redding, Stephen J; Schott, Peter K (American Economic Review, 2010)
This paper examines the frequency, pervasiveness, and determinants of product switching by US manufacturing firms. We find that one-half of firms alter their mix of five-digit SIC products every five years, that product switching is correlated with both firm- and firm-product attributes, and that product adding and dropping induce large changes in firm scope. The behavior we observe is consistent with a natural generalization of existing theories of industry dynamics that incorporates endogenous product selection within firms. Our findings suggest that product switching contributes to a reallocation of resources within firms toward their most efficient use. (JEL L11, L21, L25, L60)